‘End the cage age’: review of technical issues associated with the replacement of farrowing crates for sows and proposals for harmonized legislation - Baxter, Emma M.; Moustsen, Vivi A.; Boyle, Laura Ann; Edwards, Sandra A. (Frontiers in Animal Science, 2025)
There is pressure to ban the use of farrowing crates. Without a consensus on acceptable alternative systems, commercial progress is delayed and there are risks of fragmented legislation and building of systems that function less well. There is an urgent need for coherent, effective measures to stimulate forward progress. The main technical points of contention are the allowance of temporary crating and confinement time, pen space, enrichment and flooring. We present a multi-criteria review of these issues, designed to be of use to policymakers and other stakeholders. This review synthesizes the European Food Safety Authority (EFSA) recommendations, the latest scientific evidence base and commercial experience. We discuss potential alternatives and recommend actions for the regulation of close-confinement farrowing and lactation systems. We propose a minimum pen footprint of 6.5m2 with linear distances to support unhindered turning by the sow and, when using temporary crating, this should be for no more than 5 days. Flooring type and enrichment provision interact, with regional climatic differences making harmonized legislation about the best options not feasible. The compromises inherent in trying to meet all stakeholder’ needs may result in legislation which seemingly only makes a relatively small difference to the welfare of an individual sow and litter, but a large population of animals will benefit, making the overall increase in pig welfare considerable.